1996
DOI: 10.1093/ejo/18.6.571
|View full text |Cite
|
Sign up to set email alerts
|

Airway dimensions and head posture in obstructive sleep apnoea

Abstract: The present cephalometric study aimed to describe the antero-posterior diameters of the pharyngeal airway in a sample of 50 male obstructive sleep apnoea (OSA) patients and a reference sample of 103 male students, and to examine the relationship between these diameters and the posture of the head and the cervical column. Subjects were recorded in the cephalometer standing with the head in its natural position (mirror position). Pharyngeal airway diameters were measured at seven levels ranging from the maxillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…[32]. The width of the PAS was measured as the narrowest distance between the base of the tongue and the posterior pharyngeal wall, which is not related to any skeletal structures [33]. This value increased from 5 ± 2.2 mm to 9.5 ± 3.3 mm, replicating the findings of other studies [13] and thus demonstrating that the dimension of the airway increased after surgery.…”
Section: Discussionsupporting
confidence: 60%
“…[32]. The width of the PAS was measured as the narrowest distance between the base of the tongue and the posterior pharyngeal wall, which is not related to any skeletal structures [33]. This value increased from 5 ± 2.2 mm to 9.5 ± 3.3 mm, replicating the findings of other studies [13] and thus demonstrating that the dimension of the airway increased after surgery.…”
Section: Discussionsupporting
confidence: 60%
“…Most of these studies agree that patients with obstructive sleep apnoea have an extended head posture [12, 2431]. …”
Section: Introductionmentioning
confidence: 92%
“…It was found that the horizontal and vertical dimensions of the first cervical vertebra (C1), atlas, were associated with head posture, cranial base angulation, and mandibular shape and growth [1–4]. Also, posture of the head and neck was associated with factors such as craniofacial morphology including the cranial base [511], upper airway space [9, 12, 13], to some extent occlusion [14, 15], and temporomandibular disorders [16–21]. Many cross-sectional studies agree on a relationship between extended head posture and craniofacial structures [1, 510].…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence differential may be associated with the head position. It has been reported that the OSA subjects have an increased cranio-cervical angle in comparison with non-OSA subjects (14,15). This compensatory physiological postural mechanism to maintain airway adequacy may create an additional load on to the cervical region.…”
Section: Prevalence Of Calcification In the Nuchal Ligament And Osteomentioning
confidence: 99%